Selenium accumulation in Clorella vulgaris biomass grown under different trophic states for food supplementation - Pires, Rita Isabel Lucas (2022)
Almost all European countries, including Portugal, have soils with low selenium (Se) concentrations. This mineral has antioxidant and chemoprotective functions essential for the human immune system. Despite Se being mostly supplied in the inorganic form, organic Se is more rapidly assimilated by the organism, presenting lower toxicity. Microalgae can incorporate inorganic Se and transform it into less toxic organic forms. Therefore, C. vulgaris biomass was tested as a biological carrier for organic Se. For this purpose, C. vulgaris was cultivated under two different trophic regimes (auto- and heterotrophic) and sodium selenate (Na2SeO4) concentrations. The optimal Na2SeO4 concentration for autotrophic cultivation was 20 mg.L-1. In this case, from the 1.2% Se absorbed by the biomass, 81% was organic. The components of Seenriched biomass compared with the non-supplemented were similar (41 vs42% proteins, and 5.3 vs 6.2% lipids, respectively), except for carbohydrates (0.64 vs 2.6%, respectively). C18:1 and C18:0 compounds were the major lipids present, and differences were observed in both conditions' fatty acid profiles. The same happened for monosaccharides, and glucose was the main monosaccharide. The pigments (Chl a, Chl b, and total carotenoids) were similar for both conditions. All potential toxic metals were below the limits regulated by the European Union. Under the optimal Se concentration for autotrophic C. vulgaris growth, most of the selenium added was converted into an organic form: 0.72 g biomass would be enough to satisfy daily Se requirements. C. vulgaris showed a high potential to be used as a biofortified food to correct or prevent Se deficiency-related diseases.